Bandwidth-tuned Mott transition and superconductivity in moiré WSe2 - Yiyu Xia; Zhongdong Han; Jiacheng Zhu; Yichi Zhang; Patrick Knüppel; Kenji Watanabe; Takashi Taniguchi; Kin Fai Mak; Jie Shan (Nature, 2026)
Abstract The emergence of high-transition-temperature ( T c ) superconductivity in strongly correlated materials remains the main unsolved problem in physics. High- T c materials, such as cuprates, are generally complex and not easily tunable, making theoretical modelling difficult. Although the Hubbard model—a simple theoretical model of interacting electrons on a lattice—is believed to capture the essential physics of high- T c materials 1–5 , obtaining accurate solutions of the model, especially in the relevant regime of moderate correlation, is challenging 6 . The recent demonstration of robust superconductivity in moiré WSe 2 (refs. 7,8 ), in which low-energy electronic bands can be described by the Hubbard model and are highly tunable 9–11 , presents a new platform for studying the high- T c problem. Here we tune moiré WSe 2 bilayers to the moderate correlation regime through the twist angle and map the phase diagram around one hole per moiré unit cell ( ν = 1) by electrostatic gating and electrical transport and magneto-optical measurements. We observe a range of high- T c phenomenology, including an antiferromagnetic insulator at ν = 1, superconducting domes on electron and hole doping, and unusual metallic states such as strange metals 12–14 . Twist-angle dependence studies further show that the highest T c always occurs adjacent to the Mott transition 3,15 . Our results indicate strong correlation as the key to superconductivity in moiré WSe 2 and establish a new material system for studying high- T c superconductivity in a controllable manner.